Time spent on social media use and BMI z‐score: A cross‐sectional explanatory pathway analysis of 10798 14‐year‐old boys and girls. Issue 5 (8th March 2023) - Foubister, Campbell; Jago, Russell; Sharp, Stephen J.; van Sluijs, Esther M. F.
Summary: Background: The association between adolescent time spent on social media use and body mass index z‐score (BMI z‐score) is unclear. Pathways of association and sex differences are also unclear. This study examined the association between time spent on social media use and BMI z‐score (primary objective) and potential explanatory pathways (secondary objective) for boys and girls. Methods: Data are from 5332 girls and 5466 boys aged 14 years in the UK Millennium Cohort Study. BMI z‐score was regressed on self‐reported time spent on social media use (h/day). Potential explanatory pathways explored included dietary intake, sleep duration, depressive symptoms, cyberbullying, body‐weight satisfaction, self‐esteem, and well‐being. Sex‐stratified multivariable linear regression and structural equation modelling were used to examine potential associations and explanatory pathways. Results: Using social media for ≥5 h/day (vs. <1 h/day) was positively associated with BMI z‐score for girls (β [95% CI]) (0.15 [0.06, 0.25]) (primary objective, multivariable linear regression). For girls, the direct association was attenuated when sleep duration (0.12 [0.02, 0.22]), depressive symptoms (0.12 [0.02, 0.22]), body‐weight satisfaction (0.07 [−0.02, 0.16]), and well‐being (0.11 [0.01, 0.20]) were included (secondary objective, structural equation modelling). No associations were observed for boys and potential explanatory pathway variables were not examined. Conclusions: In girls, high time spent on social media use (≥5 h/day) was positively associated with BMI z‐score, and this association was partially explained by sleep duration, depressive symptoms, body‐weight satisfaction, and well‐being. Associations and attenuations between a self‐reported summary variable of time spent on social media use and BMI z‐score were small. Further research should examine whether time spent on social media use is related to other adolescent health metrics.